Latar belakang keahlian keuangan direktur utama, struktur kepemilikan yang terkonsentrasi, dan kualitas laporan keuangan pada perusahaan Indonesia - Kristiawan, Nicolas Bayu (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
One of the characteristics of the president director who plays an important role in determining the quality of financial reports is the background of the chief director's financial expertise. The main director with a financial background has a deep understanding of accounting and financial issues, better understands the risks of manipulated financial statements, gives more attention and supervision to accounting records and internal audits, and better understands the type of information investors want. The purpose of the study was to examine the effect of CEO financial expertise on financial reporting quality and the moderating effect of concentrated ownership structure on the relationship between the two variables. The population in this study were companies listed on the IDX in 2013-2018. The sample selection used random sampling with the final sample size was 92 companies and the total observations were 552 observations. The results of this study indicated that CEO financial expertise had a positive effect on financial reporting quality. Furthermore, the results of this study also showed that concentrated ownership structure weakened the positive influence of CEO financial expertise on financial reporting quality.